2021
DOI: 10.1136/bmjopen-2021-049690
|View full text |Cite
|
Sign up to set email alerts
|

Which strategy for using medical and community masks? A prospective analysis of their environmental impact

Abstract: IntroductionThe use of personal protective equipment, especially medical masks, increased dramatically during the COVID-19 crisis. Medical masks are made of synthetic materials, mainly polypropylene, and a majority of them are produced in China and imported to the European market. The urgency of the need has so far prevailed over environmental considerations.ObjectiveAssess the environmental impact of different strategies for the use of face mask.MethodA prospective analysis was conducted to assess the environ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 30 publications
1
4
0
Order By: Relevance
“…The preference of disposable masks will clearly raise environmental issues in relation to their safe disposal. As highlighted previously, the environmental impact of reusable cloth masks are significantly lower than disposable masks [57,58], particularly in low resource environments that lack clear policies and facilities for solid waste disposal [59]. Of those who continued to wear a reusable cloth mask, we found a 10% increase in the proportion of subjects who washed their masks every day.…”
Section: Plos Onesupporting
confidence: 54%
“…The preference of disposable masks will clearly raise environmental issues in relation to their safe disposal. As highlighted previously, the environmental impact of reusable cloth masks are significantly lower than disposable masks [57,58], particularly in low resource environments that lack clear policies and facilities for solid waste disposal [59]. Of those who continued to wear a reusable cloth mask, we found a 10% increase in the proportion of subjects who washed their masks every day.…”
Section: Plos Onesupporting
confidence: 54%
“…Earlier, Spennemann [28] stated that 75% of all pieces of surgical-type single-use face mask fabric decays into microfibers and are disposed of together alongside general waste, adding to the municipal waste stream, while also presenting a long-term source of microplastics in urban waste [28]. On another note, if a structurally compromised mask is being used, the plastic microfibers can probably be inhaled, which may result in health complications [29][30][31]. Reusing single-use face masks is not generally advised and should only be done when there is a shortage in face mask availability.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have reported the environmental impacts of equipment across a broad range of healthcare fields, including anaesthetic equipment (central venous catheter insertion kits; 73 drug trays; 74 laryngeal mask airways [LMAs]; 75,76 laryngoscopes; 77 and breathing circuits, face masks, LMAs, and laryngoscopes 71 ); dental equipment (burs 78 and xray systems 79 ); medical equipment (bedpans, 70 blood pressure cuffs, 80 cardiac monitoring devices, 81 custom packs for delivering infants, 82 electrophysiology catheters, 83 vaginal specula, 84 pulse oximeters, and deep vein thrombosis compression sleeves 85 ), personal pro tective equipment (surgical gowns, [86][87][88] scrub suits, 89,90 surgical drapes, 91 isolation gowns, 92,93 medical aprons, 88 face masks, 88,[94][95][96][97][98][99][100][101][102] face shields, 88 gloves, 26,88,103 and personal pro tective equipment kit 104 ), and surgical equipment (bronchoscopes; 105 endoscopic trocars, ultrasonic scalpels, arthroscopic shavers, and endoscopic haemostasis devices; 85 laparoscopic scissors, ports, and clip appliers; 106 minimallyinvasive prostate surgery devices; 107 scissors; 108 sharps containers; [109][110]…”
Section: Environmental Impacts Of Health-care Productsmentioning
confidence: 99%
“…Among studies comparing singleuse and reusable, or mixed, items (n=36), threequarters found that reusable equipment was associated with lower carbon footprint. [74][75][76][77]80,83,84,[86][87][88][89][90][91][92][93]95,96,[98][99][100]106,[108][109][110][111]114,115 Nine studies found Personal View that the carbon footprint of reusable items was equivalent to, or higher than, that of singleuse items, with key determinants including institutional reliance on coal based electricity for reprocessing reusable items; 71,73,113 stricter assumptions regarding the lifetime number of uses for reusable equipment; 104 less efficient reprocessing assumptions (eg, smaller machine loads or washing items individually); 70,78,105,112 and the comparison of multiple reusable instrument sets with a single, procedurespecific disposable set. 116 The production phase was the primary greenhouse gas emissions hotspot for singleuse equip ment, and the reprocessing phase (ie, decontamination or laundering) was the primary greenhouse gas emissions hotspot for reusable equipment.…”
Section: Environmental Impacts Of Health-care Productsmentioning
confidence: 99%